The Impact of Institutional Investors’ Holdings on Performance Sensitivity to Management Compensation in China - Min, Cheng (European Scientific Journal, ESJ, 2020)
In recent years, institutional investors have developed rapidly, and have gradually developed into a trend of growing multi-type institutional investors. Management compensation system, as an important part of corporate governance, is a system that institutional investors often pay attention to. And the performance sensitivity to management compensation can precisely measure the improvement of corporate governance of corporate investors, showing the convergence of management and shareholders’ goals. Therefore, it is meaningful to discuss the relation between institutional investor’s shareholding and company management compensationperformance sensitivity. This paper combines normative research and empirical research, combs and summarizes domestic and foreign literature, and puts forward some research hypotheses. In terms of empirical research, this paper selects Chinese listed companies as research samples to study the influence of overall institutional investors and different types of institutional investors on the performance sensitivity to listed companies’ management compensation. There is a positive correlation between the overall institutional investor’s shareholding and performance sensitivity to management compensation. Compared with trading institutional investors, stable institutional investors are more able to increase the performance sensitivity to management compensation in Chinese listed companies.